2002
DOI: 10.1046/j.1464-5491.2002.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lipoprotein(a) on restenosis after femoropopliteal percutaneous transluminal angioplasty in Type 2 diabetic patients

Abstract: Our data indicate that Lp(a) is generally lower in those with peripheral arterial occlusive disease and Type 2 diabetes than in non-diabetic individuals. The increased risk for restenosis with rising levels of Lp(a) is set at a lower Lp(a) in diabetes and may be more harmful for diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…We found significantly lower Lp(a) values in patients with T2DM than in nondiabetic patients. Consistent with this result from our study, decreased Lp(a) levels in patients with T2DM have been reported earlier when populations with a high prevalence of atherosclerotic disease were investigated [29][30][31].…”
Section: Discussionsupporting
confidence: 93%
“…We found significantly lower Lp(a) values in patients with T2DM than in nondiabetic patients. Consistent with this result from our study, decreased Lp(a) levels in patients with T2DM have been reported earlier when populations with a high prevalence of atherosclerotic disease were investigated [29][30][31].…”
Section: Discussionsupporting
confidence: 93%
“…The results of PCTA with or without stenting are better for proximal lesions, with reported primary patency rates of 90% at 1 year [10] and 85% at 4 years for iliac angioplasty, and 80% at 1 year for femoral angioplasty. Re‐stenosis rates are higher in diabetic compared with non‐diabetic patients after femoropopliteal PCTA [59] and high lipoprotein(a) levels [59] predict restenosis. Antiplatelet agents and cilostazol reduce restenosis rates after PCTA.…”
Section: Treatmentmentioning
confidence: 99%
“…Recent studies have also shown an independent association between plasma Lp(a) levels and thoracic aortic atherosclerosis (4) and ischaemic stroke (5). Plasma Lp(a) level is often higher in diabetic patients than in control subjects (6), and is independently associated with femoropoliteal percutaneous transluminal angioplasty restenosis (7) and with some typical diabetes complications such as proliferative retinopathy (8). Hyperhomocysteinemia, a consequence of disturbed methionine metabolism, also appears to be an independent risk factor for atherothrombotic events, even in diabetic subjects (9).…”
Section: Introductionmentioning
confidence: 99%